An extension of the coconut cream agar method to screen Penicillium citrinum isolates for citrinin production. (24th June 2013) - Mohamed, S.; Flint, S.; Palmer, J.; Fletcher, G. C.; Pitt, J. I.
<x xml:space="preserve">Abstract</x> Significance and Impact of the Study: Citrinin is a nephrotoxic mycotoxin produced by several species belonging to the genera Aspergillus, Penicillium and Monascus. A simple and rapid screening method was developed for screening citrinin in fungal cultures using Coconut Cream Agar (CCA) described previously. This method provides a direct indication of the presence of citrinin after four to 5 days incubation at 25°C. The method has been tested using fifteen isolates of P. citrinum and appears to be suitable for large scale screening of cultures for citrinin production. <boxed-text content-type="graphic" id="lam12102-blkfxd-0001" position="anchor" orientation="portrait"> </boxed-text>